Working girls : gender and sexuality in popular cinema - Tasker, Yvonne, 1964- (Routledge, 1998)
How has the new Hollywood' responded to the new woman'? Working Girls investigates contemporary cinema's ambivalent and complex relationship with gender and sexual dentities in the wake of feminism. Tasker addresses the versions of the working woman offered by contemporary Hollywood: spunky' heroines of action movies such as True Lies and The Long Kiss Goodnight ; female cops and FBI agents, in The Silence of the Lambs, Blue Steel and Copycat, the singer as movie-star, as typified by Barbra Streisand and Whitney Houston, and sharp-shooting cowgirls in new Westerns' such as Bad Girls and The Quick and the Dead . She also discusses the increasing prominence of women as producers and directors as well as stars and performers.